Characteristics of patients ≥10 years of age with diffuse intrinsic pontine glioma: a report from the International DIPG/DMG Registry. Issue 1 (11th June 2021) - Erker, Craig; Lane, Adam; Chaney, Brooklyn; Leary, Sarah; Minturn, Jane E; Bartels, Ute; Packer, Roger J; Dorris, Kathleen; Gottardo, Nicholas G; Warren, Katherine E; Broniscer, Alberto; Kieran, Mark W; et al.
Abstract: Background: Diffuse intrinsic pontine gliomas (DIPG) generally occur in young school-age children, although can occur in adolescents and young adults. The purpose of this study was to describe clinical, radiological, pathologic, and molecular characteristics in patients ≥10 years of age with DIPG enrolled in the International DIPG Registry (IDIPGR). Methods: Patients ≥10 years of age at diagnosis enrolled in the IDIPGR with imaging confirmed DIPG diagnosis were included. The primary outcome was overall survival (OS) categorized as long-term survivors (LTS) (≥24 months) or short-term survivors (STS) (<24 months). Results: Among 1010 patients, 208 (21%) were ≥10 years of age at diagnosis; 152 were eligible with a median age of 12 years (range 10-26.8). Median OS was 13 (2-82) months. The 1-, 3-, and 5-year OS was 59.2%, 5.3%, and 3.3%, respectively. The 18/152 (11.8%) LTS were more likely to be older ( P < .01) and present with longer symptom duration ( P < .01). Biopsy and/or autopsy were performed in 50 (33%) patients; 77%, 61%, 33%, and 6% of patients tested had H3K27M ( H3F3A or HIST1H3B ), TP53, ATRX, and ACVR1 mutations/genome alterations, respectively. Two of 18 patients with IDH1 testing were IDH1 -mutant and 1 was a LTS. The presence or absence of H3 alterations did not affect survival. Conclusion: Patients ≥10 years old with DIPG have a median survival of 13 months. LTS present with longer symptom duration and are likely to be older at presentation compared to STS. ATRX mutation rates were higher in this population than the general DIPG population.